2017
DOI: 10.1039/c7nr06110b
|View full text |Cite
|
Sign up to set email alerts
|

Laser-structured Janus wire mesh for efficient oil–water separation

Abstract: We report here the fabrication of a Janus wire mesh by a combined process of laser structuring and fluorosilane/graphene oxide (GO) modification of the two sides of the mesh, respectively, toward its applications in efficient oil/water separation. Femtosecond laser processing has been employed to make different laser-induced periodic surface structures (LIPSS) on each side of the mesh. Surface modification with fluorosilane on one side and GO on the other side endows the two sides of the Janus mesh with distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Similar structures can be obtained by single‐sided photocrosslinking (Figure f) . This concept also applies to single‐sided etching or femtosecond laser processing for Janus membrane fabrication. In these methods, the thickness of each layer was adjusted by radiation or etching time.…”
Section: Introducing Asymmetry Into Membranesmentioning
confidence: 65%
“…Similar structures can be obtained by single‐sided photocrosslinking (Figure f) . This concept also applies to single‐sided etching or femtosecond laser processing for Janus membrane fabrication. In these methods, the thickness of each layer was adjusted by radiation or etching time.…”
Section: Introducing Asymmetry Into Membranesmentioning
confidence: 65%
“…Recently, Sun et al reported the fabrication of a Janus wire mesh toward its applications in efficient oil/water separation . Laser‐induced periodic surface structure was first formed on both sides of a copper mesh by femtosecond laser processing.…”
Section: Functions and Applicationsmentioning
confidence: 99%
“…With respect to oil-water separation, conventional oil-water separation methods are limited by poor reliability, complicated preparation processes, and low reusability. The use of femtosecond laser fabrication can help to effectively overcome these limitations [101][102][103], and it was employed to fabricate an ultrathin aluminum foil to form a novel film consisting of nanostructured microporous arrays by a femtosecond laser, which can realize underwater superoleophobicity (OCA > 150°) and an oil-water separation function. In addition, microholes with a strong filtering effect for particles of different sizes were fabricated on a titanium foil by femtosecond laser microhole drilling, as shown in Figs.…”
Section: Superoleophobic Surface and Oil-water Separationmentioning
confidence: 99%